2016
DOI: 10.15252/embj.201593384
|View full text |Cite
|
Sign up to set email alerts
|

Bax assembly into rings and arcs in apoptotic mitochondria is linked to membrane pores

Abstract: Bax is a key regulator of apoptosis that, under cell stress, accumulates at mitochondria, where it oligomerizes to mediate the permeabilization of the mitochondrial outer membrane leading to cytochrome c release and cell death. However, the underlying mechanism behind Bax function remains poorly understood. Here, we studied the spatial organization of Bax in apoptotic cells using dual-color single-molecule localization-based super-resolution microscopy. We show that active Bax clustered into a broad distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
224
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(275 citation statements)
references
References 51 publications
28
224
2
Order By: Relevance
“…Regulatory interactions between Bax and other Bcl-2 proteins can only be observed in the presence of the OMM or liposomes (17,18). Recent studies suggest that Bax is inserted in mitochondrial membranes as a monomer that oligomerizes once inserted (19)(20)(21). These studies also have shown that Bcl-x L inhibits Bax by dissociating Bax oligomers.…”
mentioning
confidence: 99%
“…Regulatory interactions between Bax and other Bcl-2 proteins can only be observed in the presence of the OMM or liposomes (17,18). Recent studies suggest that Bax is inserted in mitochondrial membranes as a monomer that oligomerizes once inserted (19)(20)(21). These studies also have shown that Bcl-x L inhibits Bax by dissociating Bax oligomers.…”
mentioning
confidence: 99%
“…The timing 'before' and 'after' refers to the time at which changes are observed relative to MOMP. Adapted with permission from (Crimi and Degli Esposti 2011) More recently, the presence of large ring-like structures formed by Bax oligomers on MOM was detected in apoptotic cells (Große et al 2016;Salvador-Gallego et al 2016) (Fig. 5b).…”
Section: The Structure Of the Apoptotic Porementioning
confidence: 85%
“…Involvement of proteins other than Bax and Bak may assist in pore formation. Intriguingly, arc structures are also able to cause membrane permeabilization (Salvador-Gallego et al 2016). The existence of different Bax organization in the membrane such as ring-like, lines and arcs structures indicate that the mechanistic details of Bax/Bak-mediated permeabilization are not entirely understood.…”
Section: The Structure Of the Apoptotic Porementioning
confidence: 99%
See 2 more Smart Citations